“Keep Calm, it's just Vapour”: A Mixed Methods Investigation of Online E-Cigarette Discourse and User Perspectives in Western Australia - McCausland, Kahlia Louise (Curtin University, 2021)
The aim of this research was to understand how electronic cigarettes (e-cigarettes) are promoted, accessed, and used within a tightly regulated environment, by exploring the Australian online e-cigarette discourse, and the perspectives of e-cigarette users residing within the Greater Capital City Statistical Area of Perth, Western Australia. To achieve this aim three substudies were undertaken: a) scoping review, b) Twitter inquiry and c) qualitative inquiry.